Indeks kualitas pelayanan pernikahan di Jawa Tengah - Rosidin Rosidin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
This study aims to reveal how the wedding service quality index in Central Java, how the gap realities andexpectations of society towards services, and analyze the attributes of what priority the improvement inservice wedding in Central Java. The approach used in this study is quantitative. Testing the validity andreliability of the instrument showed some fall and after a further test entirely valid and reliable. Thenumber of samples involved in the study is 1000 obtained with quota purposive random samplingmethod. The study states: 1) Quality Index marriage services in Central Java at 79.08 categorized asgood; 2) All dimensions of service quality both tangible, reliability, responsiveness, assurance andempathy all is negative, meaning that all of society not as expected 3) gapnya biggest attribute is thattangible aspects of priority improvements on these aspects, without neglecting the other aspects